Treatment for alcohol use disorder among persons with and without HIV in a clinical care setting in the United States. (1st December 2021) - Davy-Mendez, Thibaut; Sarovar, Varada; Levine-Hall, Tory; Lea, Alexandra N.; Sterling, Stacy A.; Chi, Felicia W.; Palzes, Vanessa A.; Bryant, Kendall J.; Weisner, Constance M.; Silverberg, Michael J.; Satre, Derek D.
Abstract: Background: Alcohol use disorders (AUD) can lead to poor health outcomes. Little is known about AUD treatment among persons with HIV (PWH). In an integrated health system in Northern California, 2014–2017, we compared AUD treatment rates between PWH with AUD and persons without HIV (PWoH) with AUD. Methods: Using Poisson regression with GEE, we estimated prevalence ratios (PRs) comparing the annual probability of receiving AUD treatment (behavioral intervention or dispensed medication), adjusted for sociodemographics, psychiatric comorbidities, insurance type, and calendar year. Among PWH, we examined independent AUD treatment predictors using PRs adjusted for calendar year only. Results: PWH with AUD (N = 633; 93% men, median age 49) were likelier than PWoH with AUD (N = 7006; 95% men, median age 52) to have depression (38% vs. 21%) and a non-alcohol substance use disorder (SUD, 48% vs. 25%) (both P < 0.01). Annual probabilities of receiving AUD treatment were 45.4% for PWH and 34.4% for PWoH. After adjusting, there was no difference by HIV status (PR 1.02 [95% CI 0.94–1.11]; P = 0.61). Of treated PWH, 59% received only a behavioral intervention, 5% only a medication, and 36% both, vs. 67%, 4%, 30% for treated PWoH, respectively. Irrespective of HIV status, the most common medication was gabapentin. Among PWH, receiving AUD treatment was associated with having depression (PR 1.78 [1.51–2.10]; P < 0.01) and another SUD (PR 2.68 [2.20–3.27]; P < 0.01). Conclusions: PWH with AUD had higher AUD treatment rates than PWoH with AUD in unadjusted but not adjusted analyses, which may be explained by higher psychiatric comorbidity burden among PWH. Highlights: AUD treatment rates were higher for PWH with AUD than PWoH with AUD. Adjusted for psychiatric conditions, AUD treatment rates were similar by HIV status. Gabapentin was the most common AUD pharmacotherapy, regardless of HIV status. Depression and non-alcohol SUD were associated with AUD treatment in PWH with AUD.